1997
DOI: 10.1002/anie.199703571
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Copper Corroles: Well‐Known Complexes in a New Light

Abstract: Until very recently the Ni and Cu corroles, already described in the sixties, were regarded as the MII complexes 1 (M = Ni, Cu). Some doubt arose about this interpretation after the existence of FeIV corroles demonstrated that corroles can stabilize metals in unusual oxidation states. Thorough physical studies have now shown that the metal atoms in the Ni and Cu corroles do in fact have the formal oxidation state +III (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 48 publications
7
133
0
Order By: Relevance
“…The UV-vis spectrum of a nickel b-octaalkylcorrole exhibits an unusually weak Soret absorption, suggesting a corrole cation radical [74]. In addition, the EPR spectrum is unlike that of Ni(III) porphyrins [74]. This result may indeed be relevant to the general question of how corroles stabilize high-valent transition metals.…”
Section: Nickel(iii) Porphyrins Carbaporphyrins and Corrolesmentioning
confidence: 73%
See 2 more Smart Citations
“…The UV-vis spectrum of a nickel b-octaalkylcorrole exhibits an unusually weak Soret absorption, suggesting a corrole cation radical [74]. In addition, the EPR spectrum is unlike that of Ni(III) porphyrins [74]. This result may indeed be relevant to the general question of how corroles stabilize high-valent transition metals.…”
Section: Nickel(iii) Porphyrins Carbaporphyrins and Corrolesmentioning
confidence: 73%
“…This is consistent with experiment. The UV-vis spectrum of a nickel b-octaalkylcorrole exhibits an unusually weak Soret absorption, suggesting a corrole cation radical [74]. In addition, the EPR spectrum is unlike that of Ni(III) porphyrins [74].…”
Section: Nickel(iii) Porphyrins Carbaporphyrins and Corrolesmentioning
confidence: 93%
See 1 more Smart Citation
“…[1][2][3][4] Thee lectronic structure was later revised as afully deprotonated corrole ligand containing aCu III centre [5] due to the lack of an N-pyrrole proton by IR spectroscopy and crystallography,and the diamagnetic nature of the compound. Subsequent structural [6][7][8][9][10] and computational [11,12] studies of copper corroles with awide variety of meso and b-substituents have suggested the ground state to be best described as an antiferromagnetically coupled Cu II corrole radical cation.…”
mentioning
confidence: 99%
“…The discover of facile synthetic methodologies for the preparation of corroles with aryl groups on the three meso-carbon atoms (5,10,15-triarylcorroles) was highly influential regarding synthesis, properties, and applications. [19 -21] Indeed, the particular derivative based on corrole and a very large variety of its metal complexes [22,23] were fully characterized by X-ray crystallography, electrochemistry and diverse spectroscopic methods. This survey reveals many examples where corroles were used as the key components in catalysis, [24,25] sensing of gaseous molecules [26,27] and medicine-oriented research.…”
Section: Introductionmentioning
confidence: 99%